A Chinese practice guideline of the assisted reproductive technology strategies for women with advanced age. Issue 2 (29th May 2019) - Jiang, Li; Chen, Yaolong; Wang, Qi; Wang, Xiaoqin; Luo, Xufei; Chen, Junqiao; Han, Hongjing; Sun, Yingpu; Shen, Huan; ,
Abstract: More women postpone childbearing nowadays while female fertility begins to decline with advancing age. Furthermore, with the rolling out of the two‐child policy, there is a huge demand for a second child for Chinese aged women. There are various assisted reproductive technology (ART) strategies applied for age‐related infertility without solid evidence. On behalf of the Society of Reproductive Medicine, Chinese Medical Association, we would like to develop a Chinese guideline of ART strategies for age‐related infertility. This guideline was produced following the recommendations for standard guidelines described in the 2012 WHO Handbook for guideline development. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework was also followed. A protocol was formulated and a Guideline Development Group was formed with specialists of reproductive medicine, methodologists from Chinese GRADE working group, and patient representative. Questions regarding the ART strategies for aged infertility were formulated and 8 most important ones were chosen to be structured in PICO format (Population, Intervention, Comparison, Outcomes). Comprehensive search and review of the literature were performed and the quality of the evidence was assessed and rated based on certain criteria and be categorized as high, moderate, low, or very low. Twenty‐five recommendations were formulated among members of the Guidelines Development Group (Delphi method) basing on the overall quality of the evidence, in addition to the balance between benefits and harms, values and preferences, and resource implications. The final recommendations were agreed on by consensus during face‐to‐face meetings. This is the first Chinese practice guideline in reproductive medicine developed following the standard and scientific method.